Sensitivity of Stock Market Indices to Oil Prices: Evidence from Manufacturing Sub-Sectors in Turkey - Eksi, Ibrahim Halil; Senturk, Mehmet; Yildirim, H. Semih (Panoeconomicus, 2012)
Crude oil price is a critical cost factor for manufacturing industries that are of vital importance for economic growth. This study examines the relationship between crude oil prices and the indices of seven Turkish manufacturing sub-sectors over the period 1997:01-2009:12. The error correction model results reveal the long term causality from crude oil prices to chemical-petroleum-plastic and basic metal sub-sectors indicating that these sub-sectors are highly sensitive to crude oil prices. We find no causal relationship for other sector indices for short or long time periods.Key words: Crude oil prices, Manufacturing sub-sectors, VAR.JEL: M21, O16, R11.